Investment Bank Reputation and the Price and Quality of Underwriting Services - FANG, LILY HUA (Journal of Finance, 2005)
ABSTRACT The relation between investment bank reputation and the price and quality of bond underwriting services is studied here. After controlling for endogeneity in issuer–underwriter matching, I find that reputable banks obtain lower yields and charge higher fees, but issuers' net proceeds are higher. These relations are pronounced in the junk‐bond category, in which reputable banks' underwriting criteria are most stringent. These findings suggest that banks' underwriting decisions reflect reputation concerns, and are thus informative of issue quality. They also suggest that economic rents are earned on reputation, and thereby provide continued incentives for underwriters to maintain reputation.